RANCANG BANGUN GENERATOR TURBIN ANGIN TIPE AKSIAL KAPASITAS 200 W - Nurtjahjomulyo, Agus (BRIN Publishing, 2006)
Generator is the component of wind turbine that convert mechanical to electrical energy and has a specific character which operates at low speed rotation ( 1000 rpm). Engineering design of wind turbine generator capacity 200 W discussed in this paper represents the results of fabrication and testing of the generator as a model. The experiment showed that the generator can be producing power 200 W at rotation 450 rpm with torque about 8.5 Nm.